Ethnic Sensitivity Study of the Extrafine, Single-Inhaler, Triple Therapy Beclomethasone Dipropionate, Formoterol Fumarate, and Glycopyrronium Bromide Pressurized Metered Dose Inhaler in Japanese and Caucasian Healthy Individuals: A Randomized, Double-Blind, Single-Dose Crossover Study - Cella, Massimo; Täubel, Jörg; Delestre-Levai, Irisz; Tulard, Anne; Vele, Andrea; Georges, George (Clinical therapeutics, 2021)
•We compared the PK profile of BDP/FF/GB in Japanese vs Caucasian healthy volunteers•There was a slight elevation in some PK parameters in the Japanese subjects•However, the pharmacodynamic and safety results were similar in the two ethnicities•Dose adjustments in Japanese subjects are therefore not deemed necessary A number of single-inhaler, fixed-dose, triple combinations are available for the management of chronic obstructive pulmonary disease and/or asthma. One of these is the extrafine formulation beclomethasone dipropionate, formoterol fumarate, glycopyrronium bromide (BDP/FF/GB). Given that differences in ethnicity can result in differences in systemic exposure, we evaluated the relative pharmacokinetic (PK) profiles of BDP/FF/GB in Japanese vs Caucasian healthy volunteers to assess the need for dose adjustment. This randomized, double-blind, single-dose, 4-way crossover study recruited healthy men and women 20 to 55 years of age; for each Japanese person a Caucasian was enrolled who matched in terms of sex, age, and weight. Study treatments included BDP/FF/GB 200/12/25 and 400/12/25 μg (therapeutic), 800/48/100 μg (supratherapeutic), and placebo. PK blood samples were taken up to 24 hours for evaluation of BDP, beclomethasone 17-monopropionate (B17MP, an active metabolite of BDP), and formoterol and up to 48 h for GB. The primary objective was to characterize the PK profiles of BDP, FF, and GB after administration of a single dose of BDP/FF/GB in Caucasian and Japanese healthy volunteers in terms of the AUC0–t and Cmax of B17MP, formoterol, and GB. Of the 32 recruited participants (16 Japanese and 16 Caucasian ), 30 completed the study. A clear plasma exposure dose-response relationship was found for all 4 molecules. B17MP Cmax geometric mean ratios for Japanese vs Caucasian participants for the 3 study treatments ranged from 1.17 to 1.26, and AUC0–t ratios ranged from 1.16 to 1.22; thus, the findings were comparable between the ethnicities. Formoterol exposure was higher in Japanese than Caucasian participants (Cmax, 1.22–1.53; AUC0–t, 1.23–1.40). The GB Cmax with BDP/FF/GB 400/12/25 μg (1.09) and AUC0–t values for all three doses (0.98–1.17) were comparable in the 2 populations, but Cmax with 200/12/25 and 800/48/100 μg were higher in Japanese participants (1.32 and 1.42, respectively). Pharmacodynamic (cortisol, potassium, glucose, blood pressure, heart rate, and QT interval with the Fridericia correction) and safety profile results were similar in the 2 ethnicities, with most patients not experiencing any adverse events. Exposure to BDP/FF/GB pressurized metered dose inhaler at therapeutic and supratherapeutic doses was associated with higher plasma levels in Japanese versus Caucasian healthy volunteers. These PK differences did not translate into meaningful differences in the safety or pharmacodynamic parameters assessed in this study and were consistent with the results of other long-term (52-week) published studies. Dose adjustments in Japanese people are not deemed necessary. NCT03859414.